Niger : Request for Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2005)
This paper focuses on Niger's Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF). Authorities' reform program for 2005-07 focuses on fiscal consolidation; public and financial sector reforms; and development of social and priority sector strategies. To raise the government's contribution to domestic savings and investment, gradual reductions in fiscal imbalances will be sought in 2005-07. The structural reform agenda focuses on measures to further improve the supply response of the economy through more efficient allocation of resources and by improving economic governance.